2011
DOI: 10.1016/j.kjms.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar epidural space was narrower in parturients than that in nonpregnant women by ultrasound assessment

Abstract: Labor epidural is commonly used to provide both regional anesthesia and postoperative pain relief. Epidural space is supposed to be narrower and deeper in a parturient than that in a nonpregnant woman. The aim of this study was to explore the difference of epidural spaces between parturient and nonpregnant women by ultrasound assessment. Thirty nonpregnant female volunteers and 30 parturients undergoing labor epidurals were enrolled to receive ultrasound examination. A low-frequency (2-5 MHz) curved-array ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Obstetric patients are thus particularly predisposed to PDPH. This is also due to the increased technical difficulty encountered when performing epidural anaesthesia due to the narrowed epidural space, which may require multiple attempts and also due to straining during delivery, which can lead to CSF leakage at the dural puncture orifice [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric patients are thus particularly predisposed to PDPH. This is also due to the increased technical difficulty encountered when performing epidural anaesthesia due to the narrowed epidural space, which may require multiple attempts and also due to straining during delivery, which can lead to CSF leakage at the dural puncture orifice [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…This large quantity of patients may benefit from the reliable visualization offered by ultrasound compared to landmark identification (34,90,91). Epidural catheter placement can be aided by ultrasound, resulting in improved success rate for visualizing the dura and epidural space (49,57,59,74,85,88,(92)(93)(94). Chin et al found that ultrasoundaided imaging improves the success rate of spinal anesthesia in adults by 100% (70).…”
Section: Epidural Anesthesiamentioning
confidence: 99%
“…Whether spinal process was easily palpable or not was reported as a predictor of difficult epidural anesthesia [1]. In addition to loss of resistance technique, ultrasound or real‐time fiber‐optic‐guided technique was a new method to facilitate needle placement in the exact epidural space [2,3]. Inserting the epidural catheter is also an important step in such practices and is associated with several complications, including blood or wet tapping.…”
Section: Introductionmentioning
confidence: 99%